Positional therapy in sleep apnoea - one fits all? What determines success in positional therapy in sleep apnoea syndrome - Troester, Natascha (PLoS One, 2017)
INTRODUCTION: Positional therapy is a simple means of therapy in sleep apnoea syndrome, but due to controversial or lacking evidence, it is not widely accepted as appropriate treatment. In this study, we analysed data to positional therapy with regard to successful reduction of AHI and predictors of success. METHODS: All consecutive patients undergoing polysomnography between 2007 and 2011 were analysed. We used a strict definition of positional sleep apnoea syndrome (supine-exclusive sleep apnoea syndrome) and of therapy used. Patients underwent polysomnography initially and during follow-up. RESULTS: 1275 patients were evaluated, 112 of which had supine-exclusive sleep apnoea syndrome (AHI 5-66/h, median 13/h), 105 received positional therapy. With this treatment alone 75% (70/105) reached an AHI <5/h, in the follow-up 1 year later 37% (37/105) of these still had AHI<5/h, 46% (43/105) yielded an AHI between 5 and 10/h. Nine patient switched to APAP due to deterioration, 3 wanted to try APAP due to comfort reasons. At the last follow-up, 32% patients (34/105) were still on positional therapy with AHI <5/h. BMI was a predictor for successful reduction of AHI, but success was independent of sex, the presence of obstructive versus central sleep apnoea, severity of sleep apnoea syndrome or co-morbidities. CONCLUSION: Positional therapy may be a promising therapy option for patients with positional sleep apnoea. With appropriate adherence it yields a reasonable success rate in the clinical routine.